Downregulation of oxytocin-related genes in periodontitis - Ghafouri-Fard, Soudeh; Gholami, Leila; Nazer, Naghme; Hussen, Bashdar Mahmud; Sayad, Arezou; Hajiesmaeili, Mohammadreza (Frontiers in Molecular Neuroscience, 2022)
Periodontitis is a common oral disorder leading to tooth loss in both developed and developing regions of the world. This multifactorial condition is related with abnormal activity of several molecular pathways among them are oxytocin-related pathways. In the present work, we have enrolled 26 patients and 28 controls and assessed expression of four oxytocin-related genes, namely FOS, ITPR, RCAN1 and RGS2 in circulation and affected tissues of enrolled persons using real-time PCR. Expression of FOS was down-regulated in total periodontitis tissues compared with total control tissues (Ratio of mean expression (RME)=0.23, P value=0.03). Expression of FOS was also lower in total blood samples of patients compared with total controls. Expression of ITPR was down-regulated in total periodontitis tissues compared with total control tissues (RME=0.16, P value=0.01). Moreover, expression of ITPR was reduced in total blood samples of patients compared with controls (RME=0.25, P value=0.03). Expression of RCAN1 was down-regulated in total periodontitis tissues compared with total control tissues (RME=0.17, P value=0.01). However, expression of RCAN1 was not different in blood samples of affected versus unaffected persons. Finally, expression of RGS2 was lower in total periodontitis tissues compared with total control tissues (RME=0.24, P value=0.01), and in total blood samples of affected individuals compared with controls (RME=0.42, P value=0.05). This study provides data about the association between expressions of oxytocin related genes and presence of periodontitis. Future studies are needed to unravel the mechanistical links and find the correlation between expressions of these genes the pathological stage of periodontitis.